Seasonal variations in sources of dissolved inorganic carbon in the Godavari estuary (India) using stable carbon isotopes - R. Sreevidhya; V. R. D. Ghosh; B. S. K. Kumar; S. Pullyottum-Kavil; R. Chakrabarti; D. Cardinal; V. V. S. S. Sarma (Environmental Science and Pollution Research, 2025)

Spot-on application of fluralaner on cats produces high mortality in pyrethroid-resistant and susceptible Triatoma infestans, in comparison with spinosad and imidacloprid - Camila Vázquez-Cañás; María S. Gaspe; Gustavo F. Enriquez; Daniel D. Sánchez; Delfina Trezza-Neumayer; Bárbara L. Ojeda; Santiago Piñero; Claudia V. Vassena; Marta V. Cardinal (Veterinary Parasitology, 2025)

Assessing seasonal nitrogen transformations in the Godavari estuary, India - B. Sridevi; V. Vaury; B.S.K. Kumar; V.V.S.S. Sarma; D. Cardinal; M. Sebilo (Estuarine, Coastal and Shelf Science, 2023)

Madagascar Terrestrial Camera Survey Database 2021: A collation of protected forest camera surveys from 2007–2021 - Erin M. Wampole; Brian D. Gerber; Zach J. Farris; Jean Claude Razafimahaimodison; Mahandry Hugues Andrianarisoa; Claude Jacquot Ralazampirenena; Patricia C. Wright; C. Delaid Rasamisoa; Dean Gibson; Mathias W. Tobler; Timothy M. Eppley; Natalie Vasey; et al. (Ecology, 2022)
Madagascar is a threatened global biodiversity hotspot and conservation priority, yet we lack broad‐scale surveys to assess biodiversity across space and time. To fill this gap, we collated camera trap surveys, capturing species occurrences within Madagascar into a single standardized database. This data set includes nine distinct protected areas of Madagascar and encompasses 13 subprojects, 38 camera arrays, and 1156 sampling units (independent camera site per survey) within two important biodiversity eco‐regions: western dry deciduous forest and eastern humid rainforest. Camera surveys were conducted from June 2007 to January 2021. The final data set includes 17 unique families of mammals (Bovidae, Canidae, Cheirogaleidae, Daubentoniidae, Equidae, Eupleridae, Felidae, Hominidae, Indriidae, Lemuridae, Lepilemuridae, Muridae, Nesomyidae, Pteropodidae, Soricidae, Suidae, Tenrecidae) comprising 45 species and 27 unique families of birds (Accipitridae, Acrocephalidae, Alcedinidae, Bernieridae, Brachypteraciidae, Caprimulgidae, Cisticolidae, Columbidae, Coraciidae, Corvidae, Cuculidae, Dicruridae, Mesitornithidae, Monarchidae, Motacillidae, Muscicapidae, Numididae, Phasianidae, Rallidae, Sarothruridae, Strigidae, Sturnidae, Sulidae, Threskiornithidae, Upupidae, Vangidae, Zosteropidae) comprising 58 species. Images were processed and verified by individual project data set creators and camera operation and species tables were then collated. The final product represents the first broad‐scale freely available standardized formal faunal database for Madagascar. Data are available through this publication and at DOI: 10.5281/zenodo.5801806. These data will be useful for examining species‐level and community‐level trends in occurrence across space or time within Madagascar and globally, evaluating native and invasive species dynamics, and will aid in determining species conservation status and planning for at‐risk species. There are no copyright restrictions; please cite this paper when using the data for publication.

Impairments in reinforcement learning do not explain enhanced habit formation in cocaine use disorder - T. V. Lim; R. N. Cardinal; G. Savulich; P. S. Jones; A. A. Moustafa; T. W. Robbins; K. D. Ersche (Psychopharmacology, 2019)

Computational modelling reveals contrasting effects on reinforcement learning and cognitive flexibility in stimulant use disorder and obsessive-compulsive disorder: remediating effects of dopaminergic D2/3 receptor agents - Jonathan W. Kanen; Karen D. Ersche; Naomi A. Fineberg; Trevor W. Robbins; Rudolf N. Cardinal (Psychopharmacology, 2019)

Identifying transformational space for transdisciplinarity: using art to access the hidden third - Toddi A. Steelman; Evan Andrews; Sarah Baines; Lalita Bharadwaj; Emilie Rose Bjornson; Lori Bradford; Kendrick Cardinal; Gary Carriere; Jennifer Fresque-Baxter; Timothy D. Jardine; Ingrid MacColl; Stuart Macmillan; et al. (Sustainability Science, 2019)

Recognizing the importance of an all-inclusive approach to brown bear conservation now and into the future - Karine E. Pigeon; Etienne Cardinal; Gordon B. Stenhouse; Steeve D. Côté (Oecologia, 2017)

Staying cool in a changing landscape: the influence of maximum daily ambient temperature on grizzly bear habitat selection - Karine E. Pigeon; Etienne Cardinal; Gordon B. Stenhouse; Steeve D. Côté (Oecologia, 2016)

Silicon pool dynamics and biogenic silica export in the Southern Ocean inferred from Si-isotopes - F. Fripiat; A.-J. Cavagna; F. Dehairs; S. Speich; L. André; D. Cardinal (Ocean Science, 2011)
Silicon isotopic signatures (δ30Si) of water column silicic acid (Si(OH)4) were measured in the Southern Ocean, along a meridional transect from South Africa (Subtropical Zone) down to 57° S (northern Weddell Gyre). This provides the first reported data of a summer transect across the whole Antarctic Circumpolar Current (ACC). δ30Si variations are large in the upper 1000 m, reflecting the effect of the silica pump superimposed upon meridional water transfer across the ACC: the transport of Antarctic surface waters northward by a net Ekman drift and their convergence and mixing with warmer upper-ocean Si-depleted waters to the north. Using Si isotopic signatures, we determine different mixing interfaces: the Antarctic Surface Water (AASW), the Antarctic Intermediate Water (AAIW), and thermoclines in the low latitude areas. The residual silicic acid concentrations of end-members control the δ30Si alteration of the mixing products and with the exception of AASW, all mixing interfaces have a highly Si-depleted mixed layer end-member. These processes deplete the silicic acid AASW concentration northward, across the different interfaces, without significantly changing the AASW δ30Si composition. By comparing our new results with a previous study in the Australian sector we show that during the circumpolar transport of the ACC eastward, the δ30Si composition of the silicic acid pools is getting slightly, but significantly lighter from the Atlantic to the Australian sectors. This results either from the dissolution of biogenic silica in the deeper layers and/or from an isopycnal mixing with the deep water masses in the different oceanic basins: North Atlantic Deep Water in the Atlantic, and Indian Ocean deep water in the Indo-Australian sector. This isotopic trend is further transmitted to the subsurface waters, representing mixing interfaces between the surface and deeper layers. Through the use of δ30Si constraints, net biogenic silica production (representative of annual export), at the Greenwich Meridian is estimated to be 5.2 ± 1.3 and 1.1 ± 0.3 mol Si m−2 for the Antarctic Zone and Polar Front Zone, respectively. This is in good agreement with previous estimations. Furthermore, summertime Si-supply into the mixed layer of both zones, via vertical mixing, is estimated to be 1.6 ± 0.4 and 0.1 ± 0.5 mol Si m−2, respectively.

Silicon uptake and supply during a Southern Ocean iron fertilization experiment (EIFEX) tracked by Si isotopes - A.-J. Cavagna; F. Fripiat; F. Dehairs; D. Wolf-Gladrow; B. Cisewski; N. Savoye; L. Andrè; D. Cardinal (Limnology and Oceanography, 2011)
We studied the evolution of the isotopic composition of dissolved Si (δ 30 Si DSi ) and biogenic Si (δ 30 Si BSi ) during a diatom bloom induced by an iron fertilization experiment in a Southern Ocean (SO) eddy. Dissolved Si (DSi) consumption was clearly boosted as a result of iron addition. We estimate an apparent Si isotopic fractionation factor of 21.36% ± 0.11%, not significantly different from estimates based on in vitro incubations under Fe‐replete conditions and in agreement with previous SO studies under Fe‐depleted conditions. The temporal variations of the δ 30 Si Si are best reconstructed considering the fertilized surface waters as an open system, i.e., DSi is continuously supplied from the winter water. Using vertical diffusivity, we estimate a supply of 6.7 ± 1.2 mmol Si m −2 d −1 representing 30% ± 5% of total DSi demand. We estimate biogenic silica (BSi) production at 22.1 ± 1.8 mmol Si m −2 d −1 , similar to BSi production under natural conditions in the SO. The DSi use preceding the start of the fertilization was conservatively estimated at 49% ± 4%, and as a result of the Fe‐fertilization, a further 31% ± 4% of the initial DSi reservoir was consumed. The BSi export was estimated to be 17.4 ± 1.7 mmol Si m −2 d −1 . Our results suggest that for this study three main processes were acting significantly on δ 30 Si Si signatures, biological uptake, Si supply from subsurface, and export of BSi, and that the magnitude of production and export in such a Fe‐fertilized experiment are similar to those for natural diatom blooms occurring in the Southern Ocean.

Silicon Isotopic Fractionation by Banana (Musa spp.) Grown in a Continuous Nutrient Flow Device - S. Opfergelt; D. Cardinal; C. Henriet; X. Draye; L. André; B. Delvaux (Plant and Soil, 2006)

Diagenesis and its impact on Sr/Ca ratio in Holocene Acropora corals - A. Ribaud-Laurenti; B. Hamelin; L. Montaggioni; D. Cardinal (International Journal of Earth Sciences, 2001)